LC-MS/MS determination of 4-hydroxynimesulide, an active metabolite of nimesulide and application to bioequivalence study in Indian subjects. Issue 5 (October 2019) - Halder, Dhiman; Dan, Shubhasis; Sarkar, Pradipta; Das, Dibya; Chandra Halder, Umesh; Kumar Pal, Tapan
A simple and highly sensitive bioanalytical method was developed and validated for simultaneous quantification of nimesulide (NSD) and its active metabolite 4-hydroxy-nimesulide (M1) in human plasma by liquid chromatography-tandem mass spectrometer (LC-MS/MS) and applied in a bioequivalence study performed on Indian subjects. The bioanalytical method was carried out by LC-MS/MS with celecoxib (CXB) as an internal standard (IS) using liquid–liquid extraction technique. The chromatographic separation was performed on a reversed-phase Agilent eclipse plus C18 (75 mm × 4.6 mm, particle size 3.5 µm) column with a mobile phase of acetronitrile and water containing 5 mM ammonium formate (9:1, v/v). Method validation and clinical sample were analysed as per USFDA and EMA guidelines and results met the acceptance criteria. The lower limit of quantitation of NSD and M1 was found 10 ng/mL with a large linearity range from 10 to 6000 ng/mL for both NSD and M1 using only 100 µL of plasma and reported no matrix effect. The multiple reaction monitoring transitions of m/z 307.20 → 229.20, m/z 323.00 → 245.00 and m/z 380.20 → 316.20 were used to measure NSD, M1 and CXB (IS), respectively. The assay method was successfully applied for the simultaneous quantification of both NSD and M1 in plasma samples after oral administration of nimesulide 100 mg tablet in healthy human subjects.